2017
DOI: 10.5588/pha.16.0125
|View full text |Cite
|
Sign up to set email alerts
|

Infection control in hospitals managing drug-resistant tuberculosis in Pakistan: how are we doing?

Abstract: Ten hospitals managing drug-resistant tuberculosis (TB) in Pakistan. To assess the implementation of TB infection control (IC) practices and reasons for non-adherence to guidelines. This was a descriptive study conducted between April and October 2016 with three components: 1) non-participant observation of service delivery areas (SDAs) ( = 82) in hospitals ( = 10) using structured checklists; 2) exit interviews with 100 patients (10 per hospital); and 3) interviews with 100 health-care workers (HCWs, 10/hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 12 publications
3
20
0
Order By: Relevance
“…After reviewing titles and abstracts, 46 studies were selected for full text review. Finally, 13 articles were included in this review (Table 1) [20][21][22][23][24][25][26][27][28][29][30][31][32]. We only found observational/cross-sectional studies on the use of PPE for infectious diseases in healthcare settings in Pakistan.…”
Section: Types Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…After reviewing titles and abstracts, 46 studies were selected for full text review. Finally, 13 articles were included in this review (Table 1) [20][21][22][23][24][25][26][27][28][29][30][31][32]. We only found observational/cross-sectional studies on the use of PPE for infectious diseases in healthcare settings in Pakistan.…”
Section: Types Of Studiesmentioning
confidence: 99%
“…No clinical trials or laboratory-based studies on the use of PPE in such settings were found. Seven studies examined the use of PPE in hospital [20][21][22][23]25] and among those, two examined the PPE perceptions among medical students [24] or pharmacy students [32]. Two studies were conducted in the laboratory settings [26,27] while, four in dental settings [28][29][30][31] Two studies focused on the use of PPE for influenza [24,32], two were for tuberculosis [20,25] and nine studies were on multiple respiratory diseases, including influenza [21,22] or general infections [23,[26][27][28][29][30][31].…”
Section: Types Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In Armenia, TB care is provided through outpatient and inpatient services spread throughout the country. TB management follows WHO guidelines and services are provided free of cost under the umbrella of the National TB control program (NTCC) [11]. Since 2015, the program has strived to establish a continuing quality improvement system to raise the quality of services being provided to patients in the country [12].…”
Section: Introductionmentioning
confidence: 99%